Effect of different substrates on composting of poultry litter - Ana Carolina Amorim Orrico; Stanley Ribeiro Centurion; Romildo Marques de Farias; Marco Antonio Previdelli Orrico Junior; Rodrigo Garófallo Garcia (Revista Brasileira de Zootecnia, 2012)
The objective was to evaluate the differences between distinct types of litter material and their combinations in the dynamics of degradation on the organic matter fractions and the quality of the final compound. The treatments were established according to material used as substrate for broiler litter: treatment 1 - rice husks; 2 - sugar cane bagasse; 3 - wood shavings; 4 - wood shavings + sugar cane bagasse; 5 - rice husks + sugar cane bagasse; and 6 - Napier grass. The following variables were monitored: temperature, levels of total solids (TS), volatile solids (VS), mass and volume of the pile, fibrous fraction, and levels and reductions of N, P and K during the process. Piles formed with Napier grass and sugar cane bagasse presented the highest average temperatures during composting. The greater average reductions in TS and VS were attained in piles with sugar cane bagasse (68.12 and 73.07%, for TS and VS, respectively). The reductions of greatest volume occurred in piles with sugar cane bagasse (52.08%), followed by Napier grass (50.56%). Poultry litters composed of rice husks and wood shavings presented 13.21 and 10.23% of lignin, respectively, which contributed to the lower degradation of fibrous fraction and degradability. Substrates with lower lignin content were those with greatest organic matter degradation rate and had reduced losses of N levels during the process. Composting performance is affected by the initial substrate used to compose the poultry litter.